Effect of Heterodera cajani and Meloidogyne incognita with Fusarium udum and Bradyrhizobium japonicum on the wilt disease complex of pigeonpea - IRSHAD MA!:IMOOQ, ZAKI A. SIDDIQUI and (Indian Phytopathology, 2002)
Inoculation of 500 J2 of H. cajani caused greater damage to pigeon pea growth than 1000 J2 of M. incognita, in pot experiments. When both nematodes were inoculated together, damage to plant growth was more than the sum of the damage caused by them alone. Also, H. cajani and F. udum together caused more damage than when both nematodes were inoculated together. The greatest damage to plant growth was observed when all 3 pathogens were inoculated, while inoculation of B. japonicum with the other pathogens reduced the damage caused by them alone. Inoculation of nematodes prior to F. udum and B. japonicum was also found to be more damaging to plant growth. Inoculation of H. cajani and M. incognita, or both prior to F. udum and/or B. japonicum inoculation increased the disease severity. F. udum and B. japonicum had an adverse effect on nematode multiplication.